Crops in crises: Shocks shape smallholders' diversification in rural Ethiopia. (November 2022) - Makate, Clifton; Angelsen, Arild; Holden, Stein Terje; Westengen, Ola Tveitereid
Highlights: In Ethiopia, drought and temperature shock exposure increased the likelihood of farmers using improved seeds in the subsequent season. Flood and temperature shocks increased crop species diversification. Recurrent exposure to drought shocks hindered increased use of improved seeds and diversification of crop portfolios as adaptation actions. Farmers with small farm sizes and low asset endowments reduced improved seed use and diversification and increased reliance on local seed use following drought shock exposure. Policies addressing social inequality and supporting the seed systems farmers use are necessary to enhance seed security in the face of climatic and other shocks. Abstract: Crop diversity plays a central role in smallholder farmers' ability to cope with and adapt to shocks. Shifting crop varieties and diversifying the crop portfolio are common risk reduction strategies. This paper addresses the influence of covariate climate shocks and idiosyncratic socioeconomic shocks on crop variety use and crop species diversification by smallholder farmers using nationwide balanced panel data (2011/12, 2013/14, & 2015/16) from rural households in Ethiopia combined with village-level historical monthly rainfall and temperature data. We apply correlated random effects models, which control for time-invariant household unobservables. Past exposure to drought shocks increased the use of improved seed varieties in general and for wheat, while long-term average rainfall and lagged flood shocks enhance crop species diversity. Lagged temperature shocks increase improved seed use and crop species diversity. However, recurrent drought exposure and exposure to relatively more severe drought shocks significantly reduced overall agricultural activity. Idiosyncratic shocks, to a much lesser degree, influenced seed use and crop diversification decisions compared to covariate drought shocks. Heterogeneity analysis revealed that drought shock exposure on farmers with less than average farm sizes and other assets - compared to those better-off – increased their relative reliance on local seed use, reduced crop diversification, and reduced improved seed use. The results are robust to various sensitivity checks. Our findings are relevant for policy responses aiming to strengthen smallholders' ability to cope with and adapt to shocks: farmers' seed-based risk reduction strategies rely on access to seeds from both formal and informal seed systems, but policies addressing economic inequality are needed to enhance access to improved seeds and crop diversity for resource-poor socioeconomic groups.